Peningkatan Kapasitas KWT Ciharashas melalui Pelatihan Branding, Keuangan Sederhana, dan Digital Marketing Berbasis Teknologi Digital - Sayekti, Ayutyas; Sastrawan, Uding; Kuntari, Wien; Wana, Hermawan; Firhani R, Liisa; Adila, Jihan Zakia (ABDI MOESTOPO: Jurnal Pengabdian Pada Masyarakat, 2026)
This community service program aims to enhance the capacity of members of the Ciharashas Women Farmers Group (KWT Ciharashas) through integrated training covering branding, basic financial recording, and digital marketing. As a women-led rural business group, KWT Ciharashas produces processed products with high economic potential but faces challenges in business management, particularly in developing brand identity and utilizing digital platforms for marketing. The training employed a participatory approach, ensuring that participants not only understood the theoretical concepts but also acquired practical skills applicable to their business activities. The results indicate significant improvements in participants’ ability to conduct daily financial recording, calculate production costs, and determine selling prices accurately. Additionally, members began using digital platforms such as WhatsApp Business and Instagram to promote their products, resulting in broader market reach. The program also fostered collaboration among participants through the formation of a digital promotion team. Overall, the training successfully strengthened managerial literacy and entrepreneurial capabilities among KWT members, contributing to the group’s competitiveness in a technology-driven market environment. Continued mentoring is recommended to ensure sustainable implementation of the training outcomes in the business activities of KWT Ciharashas.